Bioconvective MHD flow of hybrid alumina-silver-water nanofluid across a moving needle containing gyrotactic microorganisms with Cattaneo-Christov heat and mass flux model - Utpal Jyoti Das; Deepjyoti Mali (Hybrid Advances)
The current study contains a steady laminar bioconvective magnetohydrodynamic (MHD) flow involving water (H2O)-based hybrid nanofluid composed of silver (Ag) and alumina oxide (Al2O3) as nanoparticles. This flow passes over a thin moving slender needle including gyrotactic motile microorganisms through a porous medium. The study examines how various physical characteristics, such as Cattaneo-Christov heat and mass flow, and viscous dissipation, affect the system's flow. Our objective is to find the impact of pertinent parameters on velocity, temperature, concentration, and microorganisms. This type of flow problem is important to control the heat and fluid flow phenomena around a needle which are applied to biotechnology (bioreactors, microbial fuel cells), biomedical engineering, microfluidics, and cooling systems. The reason for this investigation combines both scientific curiosity and practical applications. The controlling equations are simplified into nonlinear ordinary differential equations, solved numerically via MATLAB bvp4c tool, and their impact on temperature, velocity, microorganism, and concentration outline is graphically depicted, also, their impact on local microorganism's number, local Sherwood number, frictional drag coefficient, and local Nusselt number, are tabulated. This study's novelty is that it fills the gaps left by Kandasamy et al. [31]. This study demonstrates great agreement with Kandasamy et al. [31]. The study's findings indicate that improvement of thermal and concentration relaxation parameters declines fluid temperature and concentration respectively. Also, enhancement of bioconvection Lewis and Peclet numbers diminishes the microorganisms' profile. Again, when the Dufour and Soret numbers rise, then the temperature and concentration distribution also improve respectively. Furthermore, introducing 1 % of alumina oxide (Al2O3), and silver (Ag) nanoparticles into the base fluid increased frictional drag by 2.64 %, and 3.03 %, respectively, compared to water.